ANALISIS PENGGUNAAN E-MODUL UNTUK MENDUKUNG KEMAMPUAN PEMBELAJARAN FISIKA SISWA DI SMA: TINJAUAN PUSTAKA SISTEMATIK - Wulandari, Mashelin; Jumadi, Jumadi (EduFisika: Jurnal Pendidikan Fisika, 2023)
This study aims to describe the abilities possessed by students by using e-modules in learning physics at the high school level.The research method is qualitative with a systematic literature review type of research.The articles obtained were 50 articles from Google Scholar with a publication range from 2017 to 2021 as a population which were then filtered to become 10 articles indexed Sinta 1-3 as a sample. Based on the results of the analysis, it is known that the e-module is one of the teaching materials that can describe new innovations in the learning process so that it becomes more interactive and flexible. The use of e-modules in physics learning can support problem-solving abilities, higher-order thinking skills, conceptual understanding, scientific literacy, creativity, learning outcomes and student achievement. Thus, the use of e-modules in physics learning at the senior high school level can be said to be effective in an effort to optimize the objectives of the learning being carried out.